Realia poznawania języków obcych przez licealistów w dobie zjednoczonej Europy - Wojciechowska, Aleksandra (Studia Etnologiczne i Antropologiczne, 2014)
Currently, development of language and cultural competencies is of fundamental importance. Cultural education (including multiculturalism) enriches and models one’s own culture, prepares for dialogue, creates identity based on the strong sense of national values and roots while respecting and understanding others. The goal of language learning is clear: education should lead to language competence, make cultural intertwining easier and implement the basis for tolerance and openness. Cultural (multicultural) competence is a result of gaining experience (also linguistic experience) which is an ongoing process involving analysis and discovering rules rather than being a skill that one can learn.